The Impact of the Capital Market, the Insurance Sector and the Mortgage Finance Sector on Economic Growth in Egypt, 2005-2019 - Anis, Hana (AUC Knowledge Fountain, 2021)
This thesis aims to explore the relationship between financial markets and economic growth in Egypt for the 15 years period, starting from 2005 to 2019. The study concentrates on the non-banking financial sector which includes the stock market, the debt market, the mortgage and the insurance sectors. The Vector Autoregressive (VAR) model is utilized to describe the relationship between GDP growth rate, as a proxy for economic growth, and a number of variables from the financial sector. Results of the analysis show that there is a significant relationship and statistical causality between the growth rate and the debt market, represented by credit allocations to the government and credit allocations to the private sector. Results of the causality test support the supply-leading growth hypothesis, stating that causality is unidirectional and runs from the financial market to economic growth. Yet, the study indicates that the bond market, represented by outstanding treasury instruments, has no contribution in enhancing growth. These findings are attributed to the dominance of the debt market over the equity market in raising capital. Also, a positive relationship is witnessed between stock market liquidity, measured by the turnover ratio, and economic growth; while stock market size, measured by market capitalization, is found to be insignificant to growth. The latter is explained by the speculative-based decisions on which the Egyptian stock market operates, rather than investment-based decisions. Similarly, no statistical significance is identified between economic growth and the sizes of the insurance and mortgage finance sectors, measured by insurance premiums and outstanding mortgage loans, respectively. These results are justified by the insurance market’s untapped growth potential and the overlap of financial services offered by banks and financial service companies.